(untitled) (PerCursos, 2026)
Affirmative action is a policy aimed at promoting equal access to spaces historically appropriated by certain groups to the detriment of others and therefore drives social transformation. There is an important role for social movements in winning rights for vulnerable groups. Fiocruz has adopted inclusive measures in various institutional spaces and, since 2017, also in the field of stricto sensu postgraduate studies. This article presents the results of research into the impact of affirmative action in postgraduate studies at Fiocruz. At this stage, based on an analysis of the public calls for master’s degree courses, significant progress was made in terms of expanding quotas and setting up hetero-identification committees and biopsychosocial boards. The work showed that the courses are having difficulty making selection processes more flexible, which exacerbates inequalities, such as the requirement for foreign language proficiency. The allocation of scholarships to quota students, an important part of the student retention policy, appears to be an important measure to be further developed. It is understood that decisions made by educational institutions inspire other units and the role of regulations as a driving force behind the Affirmative Action Policy at Fiocruz is evident.